Prevalence of HIV-1 drug resistance in treated patients with viral load >50 copies/mL: a 2014 French nationwide study. (25th February 2017) - Assoumou, L.; Charpentier, C.; Recordon-Pinson, P.; Grudé, M.; Pallier, C.; Morand-Joubert, L.; Fafi-Kremer, S.; Krivine, A.; Montes, B.; Ferré, V.; Bouvier-Alias, M.; Plantier, J.-C.; et al.
Abstract : Background: Surveillance of HIV-1 resistance in treated patients with a detectable viral load (VL) is important to monitor, in order to assess the risk of spread of resistant viruses and to determine the proportion of patients who need new antiretroviral drugs with minimal cross-resistance. Methods: The HIV-1 protease and reverse transcriptase (RT) and integrase genes were sequenced in plasma samples from 782 consecutive patients on failing antiretroviral regimens, seen in 37 specialized centres in 2014. The genotyping results were interpreted using the ANRS v24 algorithm. Prevalence rates were compared with those obtained during a similar survey conducted in 2009. Results: The protease and RT sequences were obtained in 566 patients, and the integrase sequence in 382 patients. Sequencing was successful in 60%, 78%, 78% and 87% of patients with VLs of 51–200, 201–500, 501–1000 and >1000 copies/mL, respectively. Resistance to at least one antiretroviral drug was detected in 56.3% of samples. Respectively, 3.9%, 8.7%, 1.5% and 3.4% of patients harboured viruses that were resistant to any NRTI, NNRTI, PI and integrase inhibitor (INI). Resistance rates were lower in 2014 than in 2009. Resistance was detected in 48.5% of samples from patients with a VL between 51 and 200 copies/mL. Conclusion: In France in 2014, 90.0% of patients in AIDS care centres were receiving antiretroviral drugs and 12.0% of them had VLs >50 copies/mL. Therefore, this study suggests that 6.7% of treated patients in France might transmit resistant strains. Resistance testing may be warranted in all treated patients with VL > 50 copies/mL.